Prevalence of enterococcal groin colonization in patients undergoing cardiac interventions: challenging antimicrobial prophylaxis with cephalosporins in patients undergoing transcatheter aortic valve replacement. (November 2022) - Widmer, D.; Widmer, A.F.; Jeger, R.; Dangel, M.; Stortecky, S.; Frei, R.; Conen, A.
Summary: Background: Cephalosporins are recommended for prophylaxis before transcatheter aortic valve replacement (TAVR). Infective endocarditis (IE) after TAVR is caused by enterococci in up to 30% of cases, particularly early after TAVR. Enterococcal colonization in the groin has been postulated as a source of infection, not only because prophylaxis does not cover enterococci but also because most TAVR procedures are performed by transfemoral access. There are few data analysing the groin microbiome to demonstrate the presence of enterococci. Aim: To assess the prevalence of enterococci in the groins of cardiological patients receiving transfemoral interventions. Methods: This prospective cohort study was undertaken at University Hospital Basel, Switzerland between February and August 2020. Two skin swabs were taken from the groins of consecutive patients undergoing transfemoral cardiac interventions before the administration of antibiotic prophylaxis; for each patient, swabs were taken before and after groin disinfection. Swabs were analysed in the local microbiological laboratory following validated culture methods. Findings: Of 290 included patients, 245 (84.5%) underwent coronary angiography, 31 (10.7%) underwent TAVR, eight (2.8%) underwent right heart catheterization, five (1.7%) underwent closure of patent foramen ovale, and one (0.3%) underwent a MitraClip procedure. Enterococci were detected before disinfection in 48 patients, enterococci were still cultured after disinfection in three patients, and enterococci were detected after disinfection alone (i.e. not detected before disinfection) in one patient. The prevalence of enterococci was 16.6% before disinfection and 1.4% after disinfection. Patients colonized with enterococci had a significantly higher body mass index and were more likely to be diabetic than uncolonized patients. Conclusion: Common enterococcal colonization of the groin, coupled with frequent isolation of enterococci from patients with TAVR-associated IE, provides strong evidence that the current recommendation of antimicrobial prophylaxis with cephalosporins before TAVR should be changed to antimicrobial prophylaxis with a compound that is active against enterococci.